The correct publication date for mecopteran insects (Choristidae, Bittacidae, and Panorpidae) described by John Obadiah Westwood, resurrecting Panorpa confusa Westwood, 1841, the confused scorpionfly - Somma, Louis A. (Zootaxa, 2011)
I correct the publication dates for one genus and 14 species of Mecoptera (1 choristid, 4 bittacids, and 9 panorpids), and resurrect Panorpa confusa Westwood, 1841. Additionally, I provide a nomenclatural and taxonomic summary for these taxa, and a publication history for all of Westwood’s related publications.